Άνθης, πατρίκιος, κόμης του Οψικίου, εκ προσώπου του Κωνσταντίνου Ε' (μέσα του όγδοου αιώνα) - ΛΕΟΝΤΣΙΝΗ, Μαρία (Byzantina Symmeikta, 1996)
Maria Leontsini Anthes, patricius, count of the Opsikion and locum tenens of the emperors Constantine V and Leo IV In this brief note, some significant data are combined to reconstruct the brilliant career of a neglected high official, probably an iconoclast, who had participated in the administration of the Empire for several years in the mid-eighth century.